Get your website noticed How to reach, acquire and retain customers online - Koveshnikov, Vadim (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The Internet has developed itself as a major tool in marketing. With the advent of the Internet, online marketing has become the main marketing strategy used by most companies to promote their products. However, with the Internet, competition among companies has increased as each company has an opportunity to reach the same type of potential consumers through the Internet. This implies that for a company to attract and retain customers, it has to employ unique features in its website in order to make it stand out. This study was aimed at determining the features of a company’s website which can help to attract and retain customers. It was also meant to find out about the online marketing strategies that can be used to attract customers at the initial stage as well as find out on how companies engage their customers on their site. In this study, the qualitative method of research was used. Data collection was done using interviews. The interviewees were selected from marketing agencies in Finland